Prognostic Factors of Organophosphate Poisoning Between the Death and Survival Groups - Tzeng-Jih Lin (Kaohsiung Journal of Medical Sciences, 2007)
In this prospective case series study, we consider the different factors between death and survival groups of organophosphate poisoning. Patients in tertiary-care medical center who had been exposed to organophosphate were included in the study. Pralidoxime (PAM) was discontinued after atropine had controlled the clinical situation. We recorded the demographic data, amount of organophosphate consumption, duration of coma, duration of ventilator use, duration of hospitalization, findings of chest X-ray, white blood cell count, acetylcholinesterase concentration, plasma cholinesterase concentration, total atropine amount, duration of atropine use, total PAM amount, duration of PAM use, urine organophosphate peak concentration, duration of urine organophosphate and mortality rate. Urine was collected every 8 hours and was analyzed by gas chromatography equipped with a flame photometric detector and gas chromatography with mass spectrometer detector for organophosphate determination. The urine organophosphate peak concentration was recorded. Wilcoxon rank sum test was used to compare the factors between death and survival groups. Fisher's exact test was used to compare the different findings of chest X-ray between the death and survival groups. Evidently, the death group had a higher amount of organophosphate consumption, duration of coma, and higher white blood cell count than those in the survival group. Also, the death group had lower duration of hospitalization, and decreased concentrations of acetylcholinesterase and plasma cholinesterase. Total PAM amount use and duration of PAM use were lower. However, the duration of ventilator use, findings of chest X-ray, total atropine amount, duration of atropine, urine organophosphate peak concentration and duration of urine organophosphate were similar in both groups. The mortality rate of our 50 cases was 20%. As stated earlier, the cases of the death group had insufficient PAM therapy. The maximum duration of PAM use was shorter than the maximum duration of urine organophosphate, although the medians of duration of PAM use were more than the medians of duration of urine organophosphate in both the survival and death groups. Prolonged coma duration, lower level of acetylcholinesterase and lower level of plasma cholinesterase were related to the poor prognosis of the patients.